1995
DOI: 10.1172/jci117974
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil chemoattractants generated in two phases during reperfusion of ischemic myocardium in the rabbit. Evidence for a role for C5a and interleukin-8.

Abstract: The neutrophil chemoattractants generated in a model of myocardial infarction in the anesthetized rabbit were investigated. Coronary artery occlusion was followed by reperfusion for periods from 5 min to 4.5 h. Extracts of myocardial tissue in normal and post-ischemic zones were tested for C5a and interleukin-8 (IL-8) using specific radioimmunoassays. In the post-ischemic zone, imnunoreactive C5a was detected within 5 min and rose progressively to reach a plateau at 3-4.5 h. In contrast, immunoreactive IL-8 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(78 citation statements)
references
References 45 publications
2
74
0
1
Order By: Relevance
“…IL-8 upregulation has been documented in canine [102] and rabbit [103] models of experimental myocardial infarction. Elucidation of the role of IL-8 in cardiac injury has been hampered by the absence of an IL-8 homologue in mice.…”
Section: Chemokines In Healing Infarctionmentioning
confidence: 99%
“…IL-8 upregulation has been documented in canine [102] and rabbit [103] models of experimental myocardial infarction. Elucidation of the role of IL-8 in cardiac injury has been hampered by the absence of an IL-8 homologue in mice.…”
Section: Chemokines In Healing Infarctionmentioning
confidence: 99%
“…This is the earliest cell adhesion event following tissue insult. [37][38][39][40] Activated neutrophils participate in the cleaning of the scar, but they can also in some cases be deleterious, increasing superoxide production, free radicals, and proinflammatory cytokines. 41 Using bone marrow transplantation, we overexpressed sFRP-1 specifically in leukocytes and compared its effect on the inflammatory processes, to that in overexpression in ECs or in cardiomyocytes.…”
Section: Sfrp-1 Effects In Vivomentioning
confidence: 99%
“…In addition, others have shown that C5 and specifically, C5a, is critical for neutrophil and monocyte chemotaxis in either myocardial or mesenteric ischemic models (11)(12)(13)(14). Finally, in a renal ischemia/reperfusion model, C5a blockade prevents damage that is not dependent on neutrophil infiltration, but by alteration of the chemokine profile (13).…”
Section: Introductionmentioning
confidence: 99%